Pteridophytic Flora of Achanakmar-amarkantak Biosphere Reserve, Central India - Shukla, Achuta Nand; Singh, K. P. (Indian Forester, 2009)
The present paper deals with the systematic account of 35 species belonging to 25 genera and 18 families of Pteridophytes. Key to genera and species, along with correct nomenclature, brief description, ecological notes, and specimens examined and distributional notes have been provided for their easy identification.